Method for preparing geopolymer low-carbon cement by comprehensive utilization of multi-element solid waste and application thereof
Patent Information
- Application Number
- CN202410106896.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-25
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-01-25
AI Technical Summary
在现有技术条件下,进一步减排CO2的潜力与弹性已十分有限
[0023](1)本发明使用工业固废制备地聚物低碳水泥替代传统水泥,不仅解决固废存放对环境造成的污染,减少了固废处理处理成本,还可减少水泥生产过程中产生的CO2排放问题以及煅烧所需的大量能耗。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of industrial solid waste resource utilization, specifically relating to a method and application of preparing geopolymer low-carbon cement through comprehensive utilization of multiple solid wastes. Background Technology
[0002] Industrial wastewater from industries such as salt chemical, chlor-alkali chemical, coal chemical, hydrometallurgical, and pharmaceutical manufacturing often contains mixed solutes such as sodium chloride and sodium sulfate. If this mixed salt is directly introduced into the evaporation and crystallization system, it will generate a large amount of solid waste and incur high post-treatment costs. Salt separation is the best way to reduce the amount of mixed salt produced at the end of the process. This involves separating the components of the mixed solution to obtain sodium chloride and sodium sulfate (Glauber's salt) before evaporation and crystallization, thus reducing solid waste treatment costs. The sodium sulfate obtained from salt separation is mainly sodium sulfate decahydrate. However, due to its low purity and high impurity content, its direct application is limited.
[0003] Polyvinyl chloride (PVC) is a widely used chemical product. Due to high transportation costs and the presence of various impurities, the comprehensive utilization rate of calcium carbide slag is low, and it is typically disposed of through landfill or stockpiling. Because calcium carbide slag has high alkalinity (pH > 12), it easily causes surface and groundwater pollution, resulting in significant damage to the ecological environment. Therefore, the resource-based treatment of calcium carbide slag is urgently needed.
[0004] Fly ash is a fine ash collected from coal-fired flue gas and is a major solid waste discharged from coal-fired power plants. Stockpiled fly ash is mainly found in northern coal-producing power generation areas where production is high but utilization is low. How to further utilize newly generated fly ash and historically stored fly ash on a large scale is a very important strategic need for solid waste management.
[0005] Microsilica, also known as silica fume, is a solid waste generated during the smelting of industrial silicon or ferrosilicon alloys in electric arc furnaces. SiO2 is the main component of microsilica, typically accounting for 80%-96%. Due to its high SiO2 content, small particle size, large specific surface area, and high chemical activity, as well as its lightweight, high refractoriness, and strong reactivity, microsilica is widely used in construction and refractory materials. However, its application in these fields has been somewhat rudimentary, failing to fully utilize the superior properties of microsilica.
[0006] Chinese invention patent application CN114933427A discloses a method for preparing low-carbon cement based entirely on industrial solid waste. This invention uses steel slag, carbide slag, graphite tailings, iron tailings, and molding sand as raw materials. The materials are ball-milled and calcined according to a designed rate to obtain silicate cement clinker, which is then supplemented with a certain amount of gypsum. The cement raw materials obtained by this invention are mainly composed of industrial solid waste, and its physicochemical properties, prepared by comprehensively utilizing various industrial solid wastes, meet the requirements of GB 175-2020 "General Silicate Cement" standard.
[0007] Currently, the cement industry emits approximately 0.85-0.90 tons of CO2 per ton of clinker, with carbon emissions primarily originating from clinker production. Under current technological conditions, the potential and flexibility for further CO2 emission reduction are quite limited. Currently, fully utilizing industrial solid waste to prepare geopolymer low-carbon cement not only effectively disposes of industrial solid waste but is also the most direct way for the cement industry to reduce carbon emissions. Summary of the Invention
[0008] To address the shortcomings of existing technologies, this invention provides a method and application for the comprehensive utilization of multiple solid wastes to prepare geopolymer low-carbon cement.
[0009] To achieve the objectives of this invention, the following technical solution is adopted:
[0010] A method for preparing geopolymer low-carbon cement through comprehensive utilization of multiple solid wastes includes the following steps:
[0011] (1) Mix Glauber's salt with water, add carbide slag, stir, and obtain mixture 1;
[0012] (2) Add silica powder to mixture 1, stir, and dry to obtain composite activator dry powder;
[0013] (3) Mix the composite activator dry powder and fly ash to obtain geopolymer low-carbon cement.
[0014] Preferably, the main component of Glauber's salt in step (1) is sodium sulfate, the mass ratio of sodium sulfate to water is 1-3:10, and the mass ratio of carbide slag to sodium sulfate is 0.5-1:1.
[0015] Preferably, the mixing time in step (1) is 2-20 min, the mixing speed is 100-200 r / min, the stirring time is 5-30 min, and the stirring speed is 100-200 r / min.
[0016] Preferably, the mass ratio of the silica powder to sodium sulfate in step (2) is 0.25-0.6:1.
[0017] Preferably, the stirring speed in step (2) is 100-200 r / min, the stirring time is 10-30 min, and the drying temperature is 40-100℃.
[0018] Preferably, the mass ratio of the composite activator dry powder to fly ash in step (3) is 1:2-4.
[0019] Another object of the present invention is to provide a geopolymer low-carbon cement prepared by the above method.
[0020] Another objective of this invention is to provide the application of the geopolymer low-carbon cement prepared by the above method in mine filling and road paving.
[0021] Preferably, the application is the use of a mixture of geopolymer low-carbon cement and water at a mass ratio of 1:0.35-0.45 in mine filling and / or road paving.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) This invention uses industrial solid waste to prepare low-carbon polymer cement to replace traditional cement. This not only solves the pollution caused by solid waste storage to the environment and reduces the cost of solid waste treatment, but also reduces the CO2 emissions generated during cement production and the large amount of energy required for calcination.
[0024] (2) Unlike traditional geopolymer cement which uses acid and alkali activation, the activators used in the preparation of geopolymer low-carbon cement in this invention are all from industrial solid waste. Glauber's salt and carbide slag react chemically to obtain calcium sulfate and sodium hydroxide. Then, microsilica powder is added to obtain sodium silicate. By adjusting the mass ratio of the three, different proportions of calcium sulfate, sodium hydroxide and sodium silicate are obtained to achieve joint activation by the three activators.
[0025] (3) This invention patent makes the activator into dry powder, mixes it with fly ash and sells it directly, avoiding a series of problems that may exist in the on-site activation of traditional geopolymer cement liquid activators. Detailed Implementation
[0026] The following non-limiting embodiments are intended to enable those skilled in the art to gain a more comprehensive understanding of the present invention, but do not limit the invention in any way. The following content is merely an exemplary description of the scope of protection claimed in this application. Those skilled in the art can make various changes and modifications to the invention based on the disclosed content, and such changes should also fall within the scope of protection claimed in this application.
[0027] The industrial sodium sulfate, carbide slag, silica fume, and fly ash all come from the Ordos Electric Power Metallurgy Group. Specifically: the industrial sodium sulfate contains more than 95% sodium sulfate decahydrate by mass; the carbide slag is dry slag, with calcium hydroxide as its main component, and a calcium hydroxide content greater than 80% by mass; the silica fume is produced from ferrosilicon, and its main component is silicon dioxide, with a silicon dioxide content greater than 80% by mass, exhibiting a nanoscale spherical structure with a diameter ranging from 50 to 500 nm; the fly ash is grade F low-calcium fly ash.
[0028] The present invention will be further described below by way of specific embodiments.
[0029] Example 1
[0030] A method for preparing geopolymer low-carbon cement through comprehensive utilization of multiple solid wastes is as follows:
[0031] (1) Mix industrial sodium sulfate with water, wherein the mass ratio of sodium sulfate in sodium sulfate to water is 20:100, stir at 150 r / min for 10 min to dissolve completely, add carbide slag, wherein the mass ratio of carbide slag to sodium sulfate in sodium sulfate is 0.7:1, stir at 150 r / min for 10 min to mix completely, and obtain mixture 1;
[0032] (2) Add silica powder to mixture 1, wherein the mass ratio of silica powder to sodium sulfate in Glauber's salt is 0.45:1, stir at 150 r / min for 15 min to mix thoroughly, and then dry at 80℃ to obtain composite activator dry powder;
[0033] (3) The composite activator dry powder and fly ash are mixed in a mass ratio of 1:3 to obtain geopolymer low carbon cement.
[0034] Preparation of geopolymer low-carbon cement blocks: In industrial use, water and geopolymer low-carbon cement are mixed, with a water-to-geolithic-carbon cement mass ratio of 0.45:1. This mixture can directly replace conventional cement in construction applications such as mine filling and road paving.
[0035] Example 2
[0036] A method for preparing geopolymer low-carbon cement through comprehensive utilization of multiple solid wastes is as follows:
[0037] (1) Mix industrial sodium sulfate with water, wherein the mass ratio of sodium sulfate in sodium sulfate to water is 30:100, stir at 100r / min for 20min to dissolve completely, add carbide slag, wherein the mass ratio of carbide slag to sodium sulfate in sodium sulfate is 1:1, stir at 100r / min for 30min to mix completely, and obtain mixture 1;
[0038] (2) Add silica powder to mixture 1, wherein the mass ratio of silica powder to sodium sulfate in Glauber's salt is 0.6:1, stir at 100 r / min for 30 min to mix thoroughly, and then dry at 100℃ to obtain composite activator dry powder;
[0039] (3) The composite activator dry powder and fly ash are mixed in a mass ratio of 1:4 to obtain geopolymer low carbon cement.
[0040] Preparation of geopolymer low-carbon cement blocks: In industrial use, water and geopolymer low-carbon cement are mixed, with a water-to-geolithic-carbon cement mass ratio of 0.45:1. This mixture can directly replace conventional cement in construction applications such as mine filling and road paving.
[0041] Example 3
[0042] A method for preparing geopolymer low-carbon cement through comprehensive utilization of multiple solid wastes is as follows:
[0043] (1) Mix industrial sodium sulfate with water, wherein the mass ratio of sodium sulfate in sodium sulfate to water is 10:100, stir at 200 r / min for 2 min to dissolve completely, add carbide slag, wherein the mass ratio of carbide slag to sodium sulfate in sodium sulfate is 0.7:1, stir at 200 r / min for 5 min to mix completely, and obtain mixture 1;
[0044] (2) Add silica powder to mixture 1, wherein the mass ratio of silica powder to sodium sulfate in Glauber's salt is 0.25:1, stir at 200 r / min for 10 min to mix thoroughly, and then dry at 40℃ to obtain composite activator dry powder;
[0045] (3) The composite activator dry powder and fly ash are mixed in a mass ratio of 1:2 to obtain geopolymer low carbon cement.
[0046] Preparation of geopolymer low-carbon cement blocks: In industrial use, water and geopolymer low-carbon cement are mixed, with a water-to-geolithic-carbon cement mass ratio of 0.45:1. This mixture can directly replace conventional cement in construction applications such as mine filling and road paving.
[0047] Example 4
[0048] A method for preparing geopolymer low-carbon cement through comprehensive utilization of multiple solid wastes is as follows:
[0049] (1) Mix industrial sodium sulfate with water, wherein the mass ratio of sodium sulfate in sodium sulfate to water is 20:100, stir at 150 r / min for 10 min to dissolve completely, add carbide slag, wherein the mass ratio of carbide slag to sodium sulfate in sodium sulfate is 0.7:1, stir at 150 r / min for 10 min to mix completely, and obtain mixture 1;
[0050] (2) Add silica powder to mixture 1, wherein the mass ratio of silica powder to sodium sulfate in Glauber's salt is 0.3:1, stir at 150 r / min for 15 min to mix thoroughly, and then dry at 80℃ to obtain composite activator dry powder;
[0051] (3) The composite activator dry powder and fly ash are mixed in a mass ratio of 1:3 to obtain geopolymer low carbon cement.
[0052] Preparation of geopolymer low-carbon cement blocks: In industrial use, water and geopolymer low-carbon cement are mixed, with a water-to-geolithic-carbon cement mass ratio of 0.45:1. This mixture can directly replace conventional cement in construction applications such as mine filling and road paving.
[0053] Example 5
[0054] A method for preparing geopolymer low-carbon cement through comprehensive utilization of multiple solid wastes is as follows:
[0055] (1) Mix industrial sodium sulfate with water, wherein the mass ratio of sodium sulfate in sodium sulfate to water is 20:100, stir at 150 r / min for 10 min to dissolve completely, add carbide slag, wherein the mass ratio of carbide slag to sodium sulfate in sodium sulfate is 0.7:1, stir at 150 r / min for 10 min to mix completely, and obtain mixture 1;
[0056] (2) Add silica powder to mixture 1, wherein the mass ratio of silica powder to sodium sulfate in Glauber's salt is 0.45:1, stir at 150 r / min for 15 min to mix thoroughly, and then dry at 80℃ to obtain composite activator dry powder;
[0057] (3) The composite activator dry powder and fly ash are mixed in a mass ratio of 1:4 to obtain geopolymer low carbon cement.
[0058] Preparation of geopolymer low-carbon cement blocks: In industrial use, water and geopolymer low-carbon cement are mixed, with a water-to-geolithic-carbon cement mass ratio of 0.45:1. This mixture can directly replace conventional cement in construction applications such as mine filling and road paving.
[0059] Example 6
[0060] A method for preparing geopolymer low-carbon cement through comprehensive utilization of multiple solid wastes is as follows:
[0061] (1) Mix industrial sodium sulfate with water, wherein the mass ratio of sodium sulfate in sodium sulfate to water is 20:100, stir at 150 r / min for 10 min to dissolve completely, add carbide slag, wherein the mass ratio of carbide slag to sodium sulfate in sodium sulfate is 0.7:1, stir at 150 r / min for 10 min to mix completely, and obtain mixture 1;
[0062] (2) Add silica powder to mixture 1, wherein the mass ratio of silica powder to sodium sulfate in Glauber's salt is 0.45:1, stir at 150 r / min for 15 min to mix thoroughly, and then dry at 80℃ to obtain composite activator dry powder;
[0063] (3) The composite activator dry powder and fly ash are mixed in a mass ratio of 1:3 to obtain geopolymer low carbon cement.
[0064] Preparation of geopolymer low-carbon cement blocks: In industrial use, water and geopolymer low-carbon cement are mixed, with a mass ratio of water to geopolymer low-carbon cement of 0.35:1. This mixture can directly replace conventional cement in construction applications such as mine filling and road paving.
[0065] Comparative Example 1
[0066] The difference from Example 1 is that in step (1), the mass ratio of calcium carbide slag to sodium sulfate in Glauber's salt is 0.2:1, and all other conditions are the same.
[0067] Comparative Example 2
[0068] The difference from Example 1 is that in step (1), the mass ratio of calcium carbide slag to sodium sulfate in Glauber's salt is 1.2:1, and all other conditions are the same.
[0069] Comparative Example 3
[0070] The difference from Example 1 is that in step (2), the mass ratio of microsilica powder to sodium sulfate in Glauber's salt is 0.15:1, and all other conditions are the same.
[0071] Comparative Example 4
[0072] The difference from Example 1 is that in step (2), the mass ratio of microsilica powder to sodium sulfate in Glauber's salt is 0.8:1, and all other conditions are the same.
[0073] Comparative Example 5
[0074] The difference from Example 1 is that the mass ratio of composite activator dry powder to fly ash in step (3) is 1:1.5, and all other conditions are the same.
[0075] Comparative Example 6
[0076] The difference from Example 1 is that the mass ratio of composite activator dry powder to fly ash in step (3) is 1:3.5, and all other conditions are the same.
[0077] Effect test
[0078] The properties of the geopolymer low-carbon cement blocks prepared in Examples 1-6 and Comparative Examples 1-6 were tested. The tests were conducted according to the method specified in GB / T17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)". First, standard specimens of 40mm × 40mm × 160mm were prepared and cured for 28 days under standard curing conditions (temperature 20±1℃ and relative humidity above 90% within 1 day). Then, compressive strength tests were performed. The test results are shown in Table 1 below.
[0079] Table 1 Test Results
[0080]
[0081] According to the results in Table 1, compared with Example 1, Comparative Example 1 has a lower calcium carbide slag content, resulting in less sodium hydroxide generated from the reaction with Glauber's salt, and less calcium hydroxide content in the calcium carbide slag. Consequently, the activation effect is poor and the overall strength of the geopolymer cement is lower.
[0082] Compared with Example 1, Comparative Example 2 had an excessive amount of calcium carbide slag, resulting in an excess of calcium carbide slag during the reaction with sodium sulfate. Consequently, the amount of sodium hydroxide produced was relatively less than that of calcium hydroxide. Since the activation effect of calcium hydroxide was weaker than that of sodium hydroxide, the final activation effect was poor, and the overall strength of the geopolymer cement was lower.
[0083] Compared to Example 1, Comparative Example 3 had a lower content of microsilica powder, which prevented the formation of sufficient sodium silicate with sodium hydroxide. Since sodium silicate provides early strength and steadily increases the strength of the geopolymer cement, the insufficient sodium silicate in Comparative Example 3 resulted in lower strength of the geopolymer cement.
[0084] Compared with Example 1, Comparative Example 4 had a higher content of silica fume, and some of it remained after the reaction with sodium hydroxide was complete. As a result, the multi-element activation of sodium hydroxide and sodium silicate could not be carried out, and the activation effect was relatively poor, resulting in lower strength of the geopolymer cement.
[0085] Compared with Example 1, Comparative Example 5 has a higher quality of composite activator dry powder and fly ash, resulting in a higher activator content and a more intense activation process. Although this can increase the overall strength and hardness, it can also lead to the inability of internal moisture to evaporate in time, resulting in a large number of cracks and a decrease in strength in the later stage.
[0086] Compared with Example 1, Comparative Example 6 had a lower strength of geopolymer cement because the mass ratio of composite activator dry powder to fly ash was lower, resulting in less activator and a poorer activating effect.
[0087] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.
Claims
1. A method for preparing geopolymer low-carbon cement through comprehensive utilization of multiple solid wastes, characterized in that, The steps are as follows: (1) Mix sodium sulfate with water, add carbide slag, stir, and obtain mixture 1; (2) Add silica powder to mixture 1, stir, and dry to obtain composite activator dry powder; (3) Mix the composite activator dry powder and fly ash to obtain geopolymer low-carbon cement; The main component of Glauber's salt in step (1) is sodium sulfate, the mass ratio of sodium sulfate to water is 1-3:10, the mass ratio of carbide slag to sodium sulfate is 0.5-1:1, the mixing time is 2-20 min, the mixing speed is 100-200 r / min, the stirring time is 5-30 min, and the stirring speed is 100-200 r / min; In step (2), the mass ratio of silica powder to sodium sulfate is 0.25-0.6:1, the stirring speed is 100-200 r / min, the stirring time is 10-30 min, and the drying temperature is 40-100℃. The mass ratio of the composite activator dry powder to fly ash in step (3) is 1:2-4.
2. A geopolymer low-carbon cement prepared by the method of claim 1.
3. The application of the geopolymer low-carbon cement prepared by the method of claim 1 in mine filling and / or road paving.
4. The application according to claim 3, characterized in that, The application refers to the use of a mixture of geopolymer low-carbon cement and water at a mass ratio of 1:0.35-0.45 in mine filling and / or road paving.
Citation Information
Patent Citations
A method for preparing low-carbon cement based on industrial solid waste
CN114933427A
Preparation method of geopolymer building block excited by carbide slag and mirabilite
CN112939524A
Micro-silicon powder-based composite activator for geopolymer grouting material and preparation method of micro-silicon powder-based composite activator
CN114890705A